The Language of Bad Love. - Grier, David Alan (Computer (00189162), 2006)
The author discusses his experiences as a computer technical representative. In his career as a technical representative, he traveled to customer sites to do routine upgrading of operating systems, fixing software virus, training of personnel and assisting of computer managers. One experience he encountered was the problem in a hospital's network system which was using the Cobol program. The hospital claimed it was operating too slow. He noted the major deficiencies of the program that reduced its effectiveness as a common language. He then had to rewrite some of the program to fix the problem.